Ventricular assist devices in heart failure: how to support the heart but prevent atrophy? - Pokorný, M; Cervenka, L; Netuka, I; Pirk, J; Koňařík, M; Malý, J (Physiological research, 2014)
Ventricular assist devices (VAD) have recently established themselves as an irreplaceable therapeutic modality of terminal heart failure. Because of the worldwide shortage of donors, ventricular assist devices play a key role in modern heart failure therapy. Some clinical data have revealed the possibility of cardiac recovery during VAD application. On the other hand, both clinical and experimental studies indicate the risk of the cardiac atrophy development, especially after prolonged mechanical unloading. Little is known about the specific mechanisms governing the unloading-induced cardiac atrophy and about the exact ultrastructural changes in cardiomyocytes, and even less is known about the ways in which possible therapeutical interventions may affect heart atrophy. One aim of this review was to present important aspects of the development of VAD-related cardiac atrophy in humans and we also review the most significant observations linking clinical data and those derived from studies using experimental models. The focus of this article was to review current methods applied to alleviate cardiac atrophy which follows mechanical unloading of the heart. Out of many pharmacological agents studied, only the selective beta2 agonist clenbuterol has been proved to have a significantly beneficial effect on unloading-induced atrophy. Mechanical means of atrophy alleviation also seem to be effective and promising.
Keywords: Adrenergic beta-Agonists; atrofie; agonisté adrenergních beta-receptorů; klenbuterol; podpůrné srdeční systémy; Animals; Clenbuterol; Humans; Heart Failure; lidé; srdeční selhání; zvířata; Atrophy; Heart-Assist Devices